IMPACT OF PRICE SENSITIVITY ON REPURCHASE INTENTION IN TERMS OF PERSONALITY FEATURES - USLU, AYPAR (My University, 2018)
The aim of the study is to determine the effect of price sensitivity on the intention of repurchasing in termsof personality characteristics, and also investigate the extent to which personality characteristics affect pricesensitivity. Accordingly, the research was carried out in line with these objectives. In our research, pricesensitivity, personality traits, socio-demographic characteristics and intention to repurchase were examinedwithin the scope of marketing. The research was conducted on 519 consumers who consume soft drinks inTurkey. In the study, it was found out that price sensitivity differs from personality traits only withNeuroticism, Extraversion and Agreeableness dimensions. Furthermore, it was a variable income level, whichvaried according to the socio-demographic characteristics of the participants and the price sensitivity. Whenthe literature is examined, it is possible that this research is beneficial to practitioners and it contributes tothe academic literature, since there are few studies on the topic.

Çalışmanın amacı, kişilik özellikleri açısından fiyat duyarlılığının yeniden satın alma niyetine olan etkisini belirlemek ve kişilik özelliklerinin fiyat duyarlılığı üzerindeki etkisini incelemektir. Bu bağlamda araştırma bu amaçlar doğrultusunda yürütülmüştür. Araştırmamızda fiyat duyarlılığı, kişilik özellikleri, sosyo-demografik özellikler ve yeniden satın alma niyeti pazarlama kapsamında incelenmiştir. Araştırma, Türkiye'de alkolsüz içecek tüketen 519 tüketici üzerinde gerçekleştirilmiştir. Çalışmada, fiyat duyarlılığının kişilik özellikleri arasında Duygusal Dengesizlik, Dışadönüklük ve Uyumluluk değişkenleri ile farklılık gösterdiği saptanmıştır. Ayrıca, sosyo-demografik özellikleri açısından katılımcıların yalnızca gelir seviyesine göre fiyat duyarlılığına göre farklılık gösterdiği bulunmuştur. Literatür incelendiğinde, bu araştırmanın uygulayıcılara faydalı olması ve akademik literatüre katkı sağlayacağını söylemek mümkündür, çünkü konuyla ilgili az çalışma bulunmaktadır.
KİŞİLİK ÖZELLİKLERİ AÇISINDAN FİYAT DUYARLILIĞININ YENİDEN SATIN ALMA NİYETİ ÜZERİNE ETKİSİ
Keywords: İktisat; İşletme